UJI BEBERAPA DOSIS TRICHOKOMPOS TERHADAP PENYAKIT VIRUS KOMPLEKS, PERTUMBUHAN DAN PRODUKSI TANAMAN CABAI MERAH (Capsicum annuum L.) - Sazali, Munawir; Ali, Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
Complex virus disease on red chilli plants is a disease caused by infection of some viruses. The disease can decrease red chilli yield up to 75%. Alternative control method is to induce plant resistance by aplication of Trichoderma sp. which is applied as of Trichocompost. This study aims to study the effect of application of various doses of Trichocompost and obtain the best dose to control the disease and to increase red chilli plant’s growth and yield. This research has been conducted experimentally by using a complete random design consisting of 5 treatments (0, 50, 100, 150 dan 200 g/plant) and 4 replications. The data were analyzed statistically using analysis of variance and the mean of each treatment was compared by using Duncan 's New Multiple Range Test (DNMRT) at level 5%. The results showed that the application of some doses of Trichocompost could induce chilli plant resistance and decrease the intensity of complex virus disease and increase number of fruits and fruit weight. Dose of 150 g/plant gave a better effect in controling complex virus disease as much as 62,62% and increase height of plant, number of fruits and fruit weight. Key words : Red chilli, complex virus, dose Trichocompost, resistance induction